Facilitative Glucose Transporters in Articular Chondrocytes - Mobasheri, A. (Springer, 2017)
Articular cartilage is a unique and highly specialized avascular connective tissue in which the availability of oxygen and glucose is significantly lower than synovial fluid and plasma. Glucose is an essential source of energy during embryonic growth and fetal development and is vital for mesenchymal cell differentiation, chondrogenesis, and skeletal morphogenesis. Glucose is an important metabolic fuel for differenti-ated chondrocytes during postnatal development and in adult articular cartilage and is a common structural precursor for the synthesis of extracellular matrix glycosaminoglycans. Glucose metabolism is critical for growth plate chondrocytes which participate in long bone growth. Glucose concentrations in articular cartilage can fluctuate depending on age, physical activity, and endocrine status. Chondro-cytes are glycolytic cells and must be able to sense the concentration of oxygen and glucose in the extracellular matrix and respond appropriately by adjusting cellu-lar metabolism. Consequently chondrocytes must have the capacity to survive in an extracellular matrix with limited nutrients and low oxygen tensions. Published data from our laboratories suggest that chondrocytes express multiple isoforms of the GLUT/SLC2A family of glucose/polyol transporters. In other tissues GLUT proteins are expressed in a cell-specific manner, exhibit distinct kinetic properties, and are developmentally regulated. Several GLUTs expressed in chondrocytes are regulated by hypoxia, hypoxia mimetics, metabolic hormones, and proinflamma-tory cytokines. In this multidisciplinary text we review the molecular and mor-phological aspects of GLUT expression and function in chondrocytes and their mesenchymal and embryonic stem cell precursors and propose key roles for these proteins in glucose sensing and metabolic regulation in cartilage.